Optimalisasi Program Labelisasi Halal Produk Makanan di Kota Palangka Raya - Kurniawan, Rahmad; Ihsan, Moh.; Ulfah, Maulida (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
Besides its natural beauty, the city of Palangka Raya also has unique culinary delights, special food, and various kinds of locally processed food products, both home and industrial. This research seeks to determine how the halal labeling program for food products is implemented in Palangka Raya, and how to optimize the halal labeling program in Palangka Raya City. This type of research is qualitative, with the research subject being the Ministry of Religion regional office managing halal labeling in the City of Palangka Raya. Data collection techniques used are observation, interviews, and documentation. Validation of data using source triangulation. Data analysis uses collection, reduction, presentation, and conclusion. The implementation of the halal labeling program in Palangka Raya City currently only covers food and beverages and does not include medicines. Thus, the implementation of the halal labeling program for food products in Palangka Raya City provides multiple benefits. The halal labeling program also has the potential to increase the competitiveness of local products in national and international markets. optimizing service programs that have been carried out by the Ministry of Religion (Kemenag) in outreach activities to the public about halal labeling. One of the optimization efforts being made is to recruit halal assistants, namely religious instructors in all regions of Indonesia, especially in Central Kalimantan.